The Relationship between Health Perception, Health Literacy, and Caring Behavior of Caregivers of Children with Acyanotic Congenital Heart Disease - Waencwaen, Namphon; Srichantaranit, Arunrat; Sanasuttipun, Wanida (Nursing Science Journal of Thailand, 2021)
Purpose: To examine the relationship between health perception, health literacy and caring behavior of caregivers of children with acyanotic congenital heart disease. Design: Descriptive correlational study. Methods: The study samples included 75 caregivers of children with acyanotic congenital heart disease aged birth to 5 years, being followed-up at three hospitals in Bangkok, and not yet having undergone cardiac surgery. The sample was selected by convenience sampling. Questionnaires used for collecting data included 1) demographic data form 2) health perception questionnaire, 3) health literacy questionnaire and 4) care of children with acyanotic congenital heart disease questionnaire (which was divided into two forms: for caregivers of children age ≤ 1 year old and for caregivers of children age > 1 year old). Data were analyzed using descriptive statistics and Spearman’s rank order correlation. Main findings: The results of the study showed that caring behavior of caregivers of children with acyanotic congenital heart disease was at a high level ( = 82.00, SD = 8.79). Health perception and health literacy of caregivers were significantly and positively correlated with caring behavior of caregivers of children with acyanotic congenital heart disease (rs = .43, p < .001, (rs = .45, p < .001 respectively). Conclusion and recommendations: According to the study findings, caregivers had a high level of caring behavior; and their caring behavior was correlated with health perception and health literacy. Therefore, nurses should improve quality and process of giving information, promote health perception and health literacy by providing easily access medical information such as the application line, and hospital website in order to enhance of the quality of care by caregivers which would assist these children to be healthy and ready for cardiac surgery.